The Method of Coating Fe3O4 with Carbon Nanoparticles to Modify Biological Properties of Oxide Measured in Vitro. (22nd November 2019) - Niemiec, Tomasz; Dudek, Mariusz; Dziekan, Natalia; Jaworski, Sławomir; Przewozik, Aleksandra; Soszka, Emilia; Koperkiewicz, Anna; Koczoń, Piotr
Abstract: The coating of nanoparticles on materials for medical application [e.g., the coating of Fe3 O4 nanopowder (IONP) with a carbon nanolayer] serves to protect and modify the selected biological, physical, and chemical properties of the coated material. Increases in chemical stability, changes in biocompatibility, and a modified surface structure are examples of the effects caused by the formation of carbon coatings. In the current study, Fe3 O4 nanoparticles were coated with a carbon nanolayer (IONP@C) in a plasmochemical reactor (using radio-frequency plasma-enhanced chemical vapor deposition methods) under various experimental conditions. Based on data from X-ray diffraction, Raman, and IR spectroscopy, the best processing parameters were determined in order to produce a carbon coating that would not change the structure of the IONP. The materials with the best cover, i.e., a uniform carbon nanolayer, were used in cytotoxic tests to investigate their biological properties using the human HepG2 hepatocarcinoma cell line and chicken embryo red blood cells as an in vitro model. The obtained results proved the low cytotoxicity of Fe3 O4 micropowder and IONP in contrast to IONP@C, which reduced cell viability, increased hemolysis, and generally was more toxic than bare Fe3 O4 .